Pressure induced stability enhancement of cubic nanostructured CeO2 - Paulin, Mariano Andrés (2020)
Ceria (CeO2)-based materials are widely used in applications such as catalysis, fuel cells and oxygen sensors. Its cubic fluorite structure with a cell parameter similar to that of silicon makes it a candidate for implementation in electronic devices. This structure is stable in a wide temperature and pressure range, with a reported structural phase transition to an orthorhombic phase. In this work, we study the structure of CeO2 under hydrostatic pressures up to 110 GPa simultaneously for the nanometer-and micrometer-sized powders as well as for a single crystal, using He as the pressure-transmitting medium. The first-order transition is clearly present for the micrometer-sized and single-crystal samples, while, for the nanometer grain size powder, it is suppressed up to at least 110 GPa. We show that the stacking fault density increases by two orders of magnitude in the studied pressure range and could act as an internal constraint, avoiding the nucleation of the high-pressure phase.